The Institutional Approach to the Fight against Corruption :The case of the National Anti-Corruption Commission of Cameroon - Kwei Haliday Nyingchia (Jurnal Hubungan Internasional, 2020)
This paper examines the organization and role of the National Anti-corruption Commission as an anti-corruption institution in Cameroon and the extent to which it can successfully fight corruption. It was carried out by comparing it with other anti-corruption institutions. A qualitative research method was adopted to analyze the case in this study. This study holds that the Commission is not independent as it is directly responsible to the Head of State. It contends that its independence and the way of appointing its members should be reviewed to fight corruption. It should equally be decentralized and given Judicial Police powers.